Species Identity and Initial Size Rather Than Neighborhood Interactions Influence Survival in a Response-Surface Examination of Competition - Shen, Zhiqiang; Li, Yuanzhi; Chen, Zhiyi; Xi, Nianxun; Luo, Wenqi; He, Qing; Liu, Songling; Lin, Wei; Zhu, Xianhui; Fang, Suqin; Wang, Youshi; Li, Buhang; et al. (Frontiers in Plant Science, 2020)
To measure intraspecific and interspecific interaction coefficients among tree species is the key to explore the underlying mechanisms for species coexistence and biodiversity maintenance in forests. Through the response surface experimental design, we established a long-term field experiment by planting 27,300 seedlings of four tree species (Erythrophleum fordii, Pinus massoniana, Castanopsis fissa, and Castanopsis carlesii) in 504 plots in different species combinations (six pairwise combinations of four species), abundance proportions (five abundance proportions of two species, i.e. A: B = 1:0, 3:1, 1:1, 1:3, 0:1), and stand densities (25, 36, 64, and 100 seedlings per plot). In this initial report, we aimed to quantify the relative importance of biotic and abiotic factors on seedling survival at the early stage of growth, which is a critical period for seedling establishment. We found that plot-level seedling survival rate was determined by species combination and their abundance proportion rather than stand density. At the individual level, individual survival probability was mainly explained by species identity, initial seedling size, and soil conditions rather than neighborhood competition. Our study highlights that the seedling intrinsic properties may be the key factors in determining seedling survival rate, while neighborhood effects were not yet prominent at the seedling life stage.